RANCANG BANGUN ALAT PENETAS TELUR AYAM OTOMATIS DENGAN PENGIRIMAN DATA VIA SMS GATEWAY BERBASIS ARDUINO NANO - Stenly Asali; Tan Suryani Sollu (Foristek, 2021)
In rural areas, free-range chickens are raised naturally, that is, the eggs are incubated by their parents directly so that the breeding of chickens is not optimal, because the native hens are only able to incubate a few eggs. Therefore an automatic chicken egg incubator is needed. Egg incubators that use automatic controllers in order to facilitate the hatching process, get maximum hatching results as expected and be able to find hatching information remotely by sending information via sms gateway. The hatching temperature is 37-380C and turning the eggs every 8 hours, starting from the eggs being put in the incubator until the eggs hatch. The data from the sensors will be processed in the diarduino and sent to the hatchery owner via SIM800L V.2 when the sound sensor detects the sound of the hatched egg. The information about the eggs that have been hatched comes from the sound sensor, even though the farmer is not in the hatchery. Experiments were carried out using 20 chicken eggs as a sample. The results of the successful hatching test were 4 chickens with a 20% success percentage, due to a power cut during the hatching process.